2017
DOI: 10.1111/jbi.12989
|View full text |Cite
|
Sign up to set email alerts
|

A phylogenomic perspective on the biogeography of skinks in the Plestiodon brevirostris group inferred from target enrichment of ultraconserved elements

Abstract: Aim The aim of our study was to reconstruct ancestral geographic distributions from time‐calibrated phylogenies generated from phylogenomic data to answer three broad questions about the biogeography of skinks in the Plestiodon brevirostris group: (1) Are biogeographic patterns correlated with the formation of the Trans‐Mexican Volcanic Belt? (2) Do different methods of phylogenetic estimation result in different topologies? If so, (3) are biogeographic reconstructions impacted by the use of different phylogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 57 publications
1
18
0
Order By: Relevance
“…Finally, our results indicate a similar pattern to previous studies in the Mexican highlands that have reported pre‐Quaternary divergence times (Bryson et al, 2017, 2018; Bryson & Riddle, 2012; Ornelas & González, 2014) and to patterns of pre‐Quaternary diversification for Neotropical species, characterized by complex mixtures of taxa that radiated and spread over a wide range of timescales (Bennett et al, 2012). These findings indicate that the origin and maintenance of a large proportion of the genetic diversity in Q. castanea have occurred within the Trans‐Mexican Volcanic Belt, which is also a hotspot for oak species diversity and has acted as a natural bridge between other biogeographic provinces (Bryson et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Finally, our results indicate a similar pattern to previous studies in the Mexican highlands that have reported pre‐Quaternary divergence times (Bryson et al, 2017, 2018; Bryson & Riddle, 2012; Ornelas & González, 2014) and to patterns of pre‐Quaternary diversification for Neotropical species, characterized by complex mixtures of taxa that radiated and spread over a wide range of timescales (Bennett et al, 2012). These findings indicate that the origin and maintenance of a large proportion of the genetic diversity in Q. castanea have occurred within the Trans‐Mexican Volcanic Belt, which is also a hotspot for oak species diversity and has acted as a natural bridge between other biogeographic provinces (Bryson et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…The analysis of the evolutionary patterns reported for the Mexican Highlands (e.g., Bryson, Linkem, & Pavón‐Vázquez, 2017; Bryson et al, 2018; Caviedes‐Solis & Leaché, 2018; Sanginés‐Franco et al, 2015; Villaseñor, Delgadillo, & Ortiz, 2006) have allowed to state hypothesis that describe the evolution of montane forests (e.g., cloud forest by Ramírez‐Barahona & Eguiarte, 2013), to describe common phylogeographical breaks limiting the species genetic structure and gene flow during different periods (Ornelas et al, 2013), and to propose the expected patterns of genetic variation in a heterogeneous geological framework mostly drove by volcanism (Mastretta‐Yanes et al, 2015). Such studies clearly illustrate the still incipient understanding of the biota evolution in a transition zone between the Nearctic and Neotropics.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic DNA was extracted from tissue samples using the Qiagen DNeasy Blood & Tissue Kit (Qiagen Inc., Valencia, CA, USA). Aliquots of extracts were shipped to RAPiD Genomics (Gainsville, FL, USA) for UCE library preparation and sequencing following Bryson et al (). Briefly, 5,472 custom‐designed probes (MYbaits; MYcroarray, Inc., Ann Arbor, MI, USA) were used to enrich 5,060 UCE loci using protocols specified in Faircloth et al ().…”
Section: Methodsmentioning
confidence: 99%
“…Libraries were sequenced on an Illumina HiSeq 3,000 (100 paired‐end) at the University of Florida ICBR Facility. Data quality filtering and assembly were performed using the phyluce pipeline (Faircloth, ) following Bryson et al (). A locus was retained in the final assembly if it was represented by >75% of taxa.…”
Section: Methodsmentioning
confidence: 99%
“…It occurs in several mountain ranges in central Mexico separated by lowland barriers and might therefore consist of multiple distinct lineages or even species. Studies of many broadly distributed highland species across this region have revealed cryptic lineages (McCormack et al, 2008; Bryson et al, 2011; Leaché et al, 2013; Navarro-Sigüenza, García-Hernández & Peterson, 2013; Mastretta-Yanes et al, 2015; Bryson Jr et al, 2017), some later described at the species level. Amphibians, it seems, are especially prone to under-splitting in the Mexican Highlands (Rovito et al, 2012; Rovito et al, 2013; Bryson Jr et al, 2018).…”
Section: Introductionmentioning
confidence: 99%